Hate Speech and Illocutionary Act on Joe Biden’s Instagram Account: A Pragmatics Approach - arfiawati, fristi (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
This research entitled Hate Speech and Illocutionary Act on Joe Biden’s Instagram Account used the theory from Austin (1962) and Brown (2019). The aim is to investigate the types of hate speech and illocutionary act of netizen’s comments on Joe Biden’s Instagram account. The study applied qualitative descriptive method and the data source was obtained by collecting the comments of netizen from the Instagram comments column of Joe Biden. The finding showed that there were 33 comments in social media. Furthermore, hate speech types comprised into 15 insulting, 4 provoking, 1 unpleasant action, 9 defamation,and 4 denigration meanwhile, illocutionary act devided into 28 assertives, 2 expressive, 1 commissive, 1 directive, and 0 declarative. The result showed that the most dominant types of hate speech is insulting with 15 data or 46%, moreover the most dominant of illocutionary act is assertive with 28 data or 85%. Thus, the comment of netizen mostly used insulting and the function of illocutionary act of assertive on Joe Biden Instagram account. Key Word: Hate Speech, Illocutionary Act, Comments, Instagram